COMPARATIVE EFFECTS OF McKenzie EXERCISES AND KENDALL EXERCISES ON FUNCTIONAL NECK DISABILITY AND PAIN IN FEMALES WITH DOWAGER’S HUMP (Journal of Medical & Health Sciences Review, 2025)
Background: Dowager’s hump, a postural deformity characterized by excessive thoracic kyphosis, leads to pain, functional disability, and compromised quality of life. Therapeutic interventions targeting musculoskeletal imbalances are critical in its management.Objective: To compare the effectiveness of McKenzie and Kendall exercises in alleviating neck pain and disability in females with Dowager’s hump.Methods: A quasi-experimental study was conducted at Physical Therapy Department of General Hospital,Faisalabad on 24 females aged 39–58 years. Participants were assigned to two experimental groups. Group A received McKenzie exercises and Group B recieved Kendall exercises. Both groups were given hot-pack therapy as a baseline intervention. Therapy was administered for 30 minutes a session for 6 consecutive weeks, three times a week. Neck Disability Index (NDI) and Visual Analogue Scale (VAS) were used pre- and post-intervention for evaluation.Results: Independent t-tests showed statistically significant differences in both VAS and NDI scores between the groups (p < 0.05), favoring McKenzie exercises.Conclusion: McKenzie exercise protocol is more effective in reducing pain and improving neck function in females with Dowager’s hump. These findings support its preferential use in clinical rehabilitation settings.